Abstracting Abstraction in Search II: Complexity Analysis - Backstrom, Christer; Jonsson, Peter (Proceedings of the International Symposium on Combinatorial Search, 2012)
Modelling abstraction as a function from the original state space to an abstract state space is a common approach in combinatorial search. Sometimes this is too restricted, though, and we have previously proposed a framework using a more flexible concept of transformations between labelled graphs. We also proposed a number of properties to describe and classify such transformations. This framework enabled the modelling of a number of different abstraction methods in a way that facilitated comparative analyses. It is of particular interest that these properties can be used to capture the concept of refinement without backtracking between levels; how to do this has been an open question for at least twenty years. In this paper, we continue our previous research by analysing the complexity of testing the various transformation properties for both explicit and implicit graph representations.